Groupwork with Refugees and Survivors of Human Rights Abuses The Power of Togetherness - Boyles, Jude; Ewart-Biggs, Robin; Horn, Rebecca; Lamb, Kirsten (Taylor & Francis, 2023)
Groupwork with Refugees and Survivors of Human Rights Abuses describes, explores and promotes the power of groupwork for refugees and survivors of human rights abuses in a range of contexts. Drawing on multiple theoretical approaches, the book features chapters from practitioners running groups in different settings, such as torture rehabilitation services, refugee camps, and reception centres. The voices of participants demonstrate the variety, creativity, and value of group and community approaches for recovery. The editors have gathered chapters into three sections covering: community-based approaches; groups that work through the medium of ""body and soul""; and group approaches that focus on change through the spoken word. The book will be relevant to those working in rehabilitation, community, mental health, and humanitarian fields and are interested in using groupwork as part of their services.